Extending the Dialogical Array - Tami Yaguri; Edward F. Mooney (Religions, 2021)
The I-You dialogue of mutually reciprocal engagement makes a difference of heaven and hell. In the first out of four suggested types of I-You dialogue discussed in this article, all the I’s—of the primary word I-You—own a dialogical perspective. In the other three, it is the I who has an experience of creating and engaging in a dialogue that shortly achieves some kind of mutuality with You. Epistemologically, the four suggested types differ by the qualities of the I who engages in dialogue. The second stance is an I-You dialogue of sympathy. A third possibility is an I-You dialogue of empathy. A fourth possibility aims higher to a dialogue that transcends human mutuality by compassion and reaches a heavenly dialogue.